Internal organisation, efficiency and profit / edited by Steve Thompson and Mike Wright - Thompson, Steve (ed.); Wright, Mike (ed.) (New Delhi, 1989)
Internal Organisation, Efficiency and Profit is an advanced text for students and speci alists in the areas of industrial economics, organisational behaviour and corporate strategy. The neo-classical theory of the firm has largely ignored its internal working and its boundaries. Yet the problem of control in large, complex organisations increasingly exercises researchers and practitioners alike. This book reviews and synthesises recent relevant literature from several disciplines including economics, management, accounting and finance. The contributor to each chapter is a leading specialist in his field.
Keywords: Organizational effectiness